PERSEPSI TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN KORUPSI ANGGARAN PENDAPATAN DAN BELANJA DAERAH - Anthonius H. Citra Wijaya (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
The study aims to analyze and test hypotheses regarding the influence of individual behavior, internal oversight and ethical Culture of the Organization against the corrupt tendencies of the regionalbudget revenue and expenditure (APBD). Respondents in this study were students of the accounting study Program at several universities located in Jayapura City. In this study the sampling method used Purposive sampling. The Data Analysis method used is multiple regression analysis and testing tools using SPSS 24. The results showed that the individual behavior variables of influential internal supervision were not significant to the tendencies of the fraud/corruption behavior OF THE APBD. In addition, the organization's ethical cultural variables have a significant positive impact on the behavioral tendencies of APBD corruption.